Modern view on the place of riociguat in the treatment of pulmonary hypertension - Z.S. Valieva; I.N. Taran; T.V. Martynyuk; I.Ye. Chazova (Терапевтический архив, 2018)
Current research is aimed at studying the fundamental therapeutic targets and discovering new drugs acting on previously set targets. Until recently, the only therapeutic strategy to influence the molecular pathway of nitric oxide (NO) – soluble guanylate cyclase (sGC) – cyclic guanosine monophosphate (cGMP) was the use of phosphodiesterase type 5 inhibitors (PDE-5 inhibitors), such as sildenafil. In September 2014, the first member of sGC stimulators riociguat was licensed in Russia. In the paper, the results of 5 multicenter studies (CHEST-1 and PATENT-1, CHEST-2 and PATENT-2, RESPITE), which reflect the effectiveness and safety of mono – and combination therapy with riociguat in patients suffer from some forms of pulmonary arterial hypertension, and patients with inoperable or persistent/recurrent chronic thromboembolic pulmonary hypertension (CTPH), as well as the possibility of optimizing therapy in patients with PAH using iPDE-5 -> riociguat switching was reviewed. It also provides information on the recently launched international registries EXPERT CTEPH; new REPLACE study was announced.